Optical Urethrotome Dislodgement during Optical Internal Urethrotomy: A Case Report of an Unexplained Event - Ammari, Bassam; Sawaqed, Fadi; Muheilan, Muheilan (Jordan Medical Journal, 2018)
Optical internal urethrotomy is a well-known, safe and effective treatment for urethral strictures postradicalprostatectomy. This case documents an unusual event that occurred during the procedure. A 68-year-old male patient was diagnosed with a urethral stricture post-radical prostatectomy. During opticalinternal urethrotomy, the blade of the urethrotome broke, after which it was removed using endoscopicforceps.